Globally stable adaptive backstepping fuzzy control for output-feedback systems with unknown high-frequency gain sign - Chen, Weisheng; Zhang, Zhengqiang (Fuzzy sets and systems, 2010)
This paper addresses the problem of globally stable adaptive backstepping output-feedback tracking control for a class of nonlinear systems with unknown high-frequency gain sign. The fuzzy systems are used as feedforward compensators to model some system functions depending on the reference signal. Thus, the global stability of closed-loop system can be guaranteed under the assumption that the unknown system functions are bounded by partly known nonlinear functions. The other advantage of the proposed control scheme is that the designer can determine the approximation domain a priori via the bound of the reference signal, which is very important for the choice of the centers and widths of membership functions. Moreover, the Nussbaum-type function is employed to deal with the unknown high-frequency gain sign. Two simulation examples are provided to illustrate the feasibility of control scheme presented in this paper.